Human Gingiva-Derived Mesenchymal Stem Cells Inhibit Xeno-Graft-versus-Host Disease via CD39–CD73–Adenosine and IDO Signals - Huang, Feng; Chen, Maogen; Chen, Weiqian; Gu, Jian; Yuan, Jia; Xue, Yaoqiu; Dang, Junlong; Su, Wenru; Wang, Julie; Zadeh, Homayoun H.; He, Xiaoshun; Rong, Limin; et al. (Frontiers in Immunology, 2017)
Mesenchymal stem cells have the capacity to maintain immune homeostasis and prevent autoimmunity. We recently reported that human-derived gingival mesenchymal stem cells (GMSCs) have strong capacity to suppress immune responses and T cell-mediated collagen-induced arthritis in animals. However, it is unclear whether these cells can suppress human T cell-mediated diseases. Here, we used a xeno-GVHD model in the NOD/SCID mouse, which is a useful preclinical construct for evaluating the therapeutic and translational potential of this approach for applications in human disease. We found that GMSCs potently suppressed the proliferation of PBMC and T cells in vitro. Co-transfer of GMSC with human PBMC significantly suppressed human cell engraftment and markedly prolonged the mouse survival. Moreover, we demonstrated that GMSCs inhibited human PBMC-initiated xenogenic responses via CD39 and IDO signals. These findings suggest the potential for GMSCs to suppress human immune responses in immune system-mediated diseases, offering a potential clinical option to be used for modulating GVHD and autoimmune diseases.